Autonomous Learning Through Chatbot-based Application Utilization to Enhance Basic Japanese Competence of Vocational High School Students - Haristiani, Nuria; Dewanty, Via Luviana; Rifai, Mumu Muhammad (Journal of Technical Education and Training, 2022)
This study sought to examine vocational students’ evaluation and feedback regarding the chatbot-based application as an assistive technology in learning basic Japanese in vocational high school and investigate students’ recommendations on the possible future advancement of the chatbot-based application to help students learn the Japanese language better. This study employed a questionnaire and follow-up interview to collect the data, which questionnaire was administered to 100 vocational students enrolled in 8 state vocational high schools located in different regions in Indonesia. The data collected were analysed using SPSS 24, and also tested for reliability and validity. The findings of this study denote the use of the chatbot-based application, namely Gengobot, useful in enhancing students’ basic Japanese grammar learning, improving vocabulary mastery related to vocational terminologies, providing practices for basic Japanese language level exercise, having attractive and interactive features, and fostering learners’ autonomy and independence learning due to its practicality, portability, accessibility, and flexibility. The results also conveyed the practicality problems and confusion in using the application as an application integrated into social media. Hence, further development of the chatbot-based application Gengobot as assistive technology in learning Japanese is recommended. All in all, the chatbot-based application Gengobot as an assistive Japanese language learning application can be concluded as compelling and is recommended to be used for vocational students to enhance autonomous learning as well as to support distance learning.